An Outline of Ethics in Translation Service Providers: A Practical Insight - Porras Acevedo, Laura Del Valle (2023)
Since the beginning of translation studies, there have been different approaches regarding translation methodologies and, through time, as the practice has become more and more globalized, the problems translators face have transcended linguistic boundaries. The birth of deontic codes and the analysis of ethical procedures have become increasingly more important within the translation world. For this reason, the central issue of this report is ethics in translation, with the purpose of creating a general consideration of what has been studied so far, regarding this topic, and focusing on specific ethical practices and deontological codes in translation, translators, and/or translation service providers. While parallelly constituting an account for an internship carried out in a translation agency (within the Master of Translation at the Polytechnic Institute of Bragança) , this report aims to link the experience of administering one of the top agencies in Ireland and working as a full-time translator, with the theoretical background of ethical studies, elaborating about the three-month experience as an Office Administrator / Translator, as well as the procedures followed within translation projects, from the moment the client appears to the conclusion of the project. Essentially, the objective is to dive into the theorical question of ethics in the world of translation within the framework of real-life experience, inquiring on the extent of moral duty when it comes to adhering to the principles espoused, i.e., how far theoretical teachings can be a guide towards a practical fulfilment of these principles, and if this is indeed feasible.